Energy Storage: Advanced Micro/Nanostructures for Lithium Metal Anodes (Adv. Sci. 3/2017) - Zhang, Rui (Adv Sci (Weinh), 2017)
Yu‐Guo Guo, Qiang Zhang, and co‐workers review the use of micro/nanostructured lithium metal anodes to retard the formation of lithium dendrites in lithium metal batteries in article 1600445. With the unique surface, pore, and connecting structures of different nanomaterials, the lithium plating/stripping processes are significantly regulated. [Image: see text]